Nation Paper Products and Printing Corporation A production and operations management study - Carrero, Geraldine T.; Ty, Laura Blossom E.; Villanueva, Farrah C. (Diliman, Quezon City College of Engineering, 1999)
Nation Paper Products and Printing Corporation (NAPPCO) is known as the pioneer producer of copy paper in the country. It produces a variety of products that can be grouped into three divisions, namely Printing, Stationery and Miscellaneous. Products include sheet s of paper used in printing books, calendars, posters and the like, cut-size papers and pad papers. A Study on NAPPCO was conducted to identify the problem areas and offer solutions and recommendations to help the company minimize delays, maximize plant capacity, improve management control over people and production and help them achieve their long term goals. After careful study of the present system, the three major problems identified by the proponents of the study were: (1) poor conduct of workers; (2) successive machines far from each other; and (3) limited number of cutting machines. In addition to these, other concerns of the company, which include forecasting, aggregate planning and strategic planning were found to have significant effect in the company's operation. To offer solutions to the identified areas of concern, the group comes up with the following proposed solutions. (1) A stricter implementation of existing policies to reduce misbehavior of workers that interfere with the production operations. And provisions of awards/incentives to boost the morale of workers and improve workmanship. (2) Rearrangement of cutting machines in the Stationery Division according to the proposed layout provided by the group so as to minimize handling of materials while improving their flow. (3) Improvement in maintenance of machines and repair of broken cutting machines to increase the capacity of the company's current production. Furthermore, with the objective of providing the company with the expected monthly demand, forecasting was performed. This forecast will serve as the basis for the company's monthly production. Also, existing aggregate planning of the company was evaluated and found out that there is a better aggregate plan that incur lesser costs. This plan which calls for a three-shift operation with no overtime, is recommended to be in use instead of the existing plan. Lastly, after determining the company's inability to meet demand even at its maximum capacity, the group suggests an expansion of the company to be able to satisfy the increasing demand for their products.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Nation Paper and Printing Corporation; Paper industry; Production engineering